Transfer of Land Rights as Wedding Gifts According to Customary Law of the Bugis Tribe in Polewali Mandar (Transfer of Land Rights as a Wedding Gift According to Bugis Tribe Customs in Polewali Mandar) - Nurul Firdaus; Benny Djaja (Greenation Research & Yayasan Global Resarch National, 2024)
In the Bugis tribal tradition, weddings typically require significant financial contributions from the groom, including panaiq money (wedding reception expenses), dowry or sompa, and gifts in the form of movable and immovable property. These gifts, such as rice fields, gardens, ponds, houses, coconut trees, and similar assets, are intended to serve as a source of livelihood for the newlyweds. Immovable property gifts, particularly land, are customarily transferred through private gift letters rather than formal deeds of gift. These private gift letters generally lack strong and definitive legal force, rendering them weak when compared to authentic documents of rights transfer, especially certificates that serve as evidence of ownership. This study employs both literature review and interview methods. The primary data source is the decision of the Polewali District Court, Case Number 32/Pdt.G/2024/PN POL, concerning a land dispute over property granted as a traditional Bugis wedding gift. The findings of this research indicate that the judge at the Polewali Mandar District Court ruled in favor of the family who granted the land as a wedding gift. The court recognized the validity of an authentic legal document, specifically a Deed of Will, over the private gift letter traditionally used in such transactions.